Energy efficient relay node fast selection algorithm for multi-hop wireless sensor networks - ZHENG Guo-qiang1; LI Jian-dong1; LI Hong-yan1; ZHOU Zhi-li4 (Tongxin xuebao, 2010)
Aiming at the inefficiency of the relay selection of data gathering protocol for multi-hop wireless sensor networks（WSN）,an energy efficient relay node fast selection（EERNFS） algorithm was proposed.In EERNFS,time-sharing channel was adopted to maintain time synchronization of WSN and periodically update the information of the neighbor network node.The network nodes could be activated synchronously in any network listening/sleeping cycle according to a certain probability,thus the real-time consistency and the stability of the nodes’ connectivity degree in WSN were guaranteed.Based on the geographic priority,the value of the nodes and the distribution estimation of the route-link quality,the relay node was selected through the competition method and the competing between the candidate relay nodes was reduced through gradually multiplying time window method.Theoretical analysis and simulation results show that EERNFS outperforms FFS（forwarder fast selection） and GeRaF in terms of energy efficiency,delay of data delivery,and data delivery rate so that the network lifetime is greatly prolonged.